Development of a TaqMan polymerase chain reaction detection method for the precise identification and quantification of an attenuated Eimeria maxima vaccine strain in poultry - Jin, Haozhan; Cai, Haiming; Liao, Shenquan; Qi, Nanshan; Li, Juan; Lv, Minna; Lin, Xuhui; Hu, Junjing; Song, Yongle; Zhu, Yibin; Chen, Xiangjie; Yin, Lijun; et al. (Frontiers in Veterinary Science, 2024)
Avian coccidiosis, a parasitic disease prevalent in poultry, is caused by Eimeria species and leads to significant economic losses. The use of attenuated live oocyst vaccines has been adopted as an alternative to the use of anticoccidial drugs. However, the accurate detection and differentiation of vaccine strains from virulent ones remain challenging. Therefore, this study presents a novel TaqMan polymerase chain reaction (PCR) detection method that offers enhanced sensitivity, specificity, and reproducibility compared with traditional PCR techniques. Through whole-genome resequencing and bioinformatics analysis, we identified a molecular marker gene, Em_marker6, with a unique 21-base pair deletion specific to the Eimeria maxima attenuated vaccine strain. Optimized primers and probes targeting this marker enabled rapid quantification cycle value achievement and high fluorescence intensity. The standard curve’s slope of −3.540 and correlation coefficient of 0.9971 confirmed precise quantification capabilities. The TaqMan PCR method detected as few as 30 plasmid DNA copies and 50 oocysts per reaction, outperforming traditional PCR techniques by an order of magnitude. No cross-reactivity was observed with other E. maxima wide-type strains or common intestinal pathogens, ensuring the exclusive detection of the E. maxima EMPY vaccine strain. Weekly testing over 3 weeks demonstrated minimal variability, indicating robust consistency in the method’s application. Testing on 61 clinical samples revealed a 57.38% positivity rate for E. maxima species and 13.11% for the vaccine strain. The Em_marker6 gene exhibited genetic stability across multiple generations, confirming the detection method’s robust stability for the attenuated E. maxima vaccine strain. This study significantly advances the field of avian coccidiosis research and control by providing a valuable tool for monitoring vaccine purity and preventing inadvertent infections in vaccinated flocks, aligning with global efforts to curb antibiotic use in animal feed.